FUZZY-FMEA APPLICATION IN COMBUSTION ENGINE VALVE FAILURE MODE CASE STUDY - AGUNG OKTAVIAN WIJAYA (NIM : 23107020); Pembimbing 1 :Dr. Ir. Arief Hariyanto; Pembimbing 2 :Prof.
Maintenance is a periodic activity or action for reconditioning a system, reducing a rate of failure, and preventing a failure propagation. Maintenance management is a control mechanism of many maintenance techniques along the maintenance process. A failure risk reduction technique during a system operation is a maintenance and operation management method. Then it will be applied to the combustion engine valve failure case study. Failure mode and effect analysis (FMEA) is a method to reduce a failure risk in a system. It has an ability to provide a risk priority number based on each failure risk. In contrast, FMEA technique has several weaknesses. One of them is its inability to facilitate a risk assessment in unique condition. So that the FMEA method then will combine with a Fuzzy Logic method. Fuzzy logic method is an inference technique that map an input into an output according to the fuzzy rules (“if-then” rules). The Fuzzy-FMEA method combine the FMEA basic procedure to the Fuzzy Logic method. The Fuzzy-FMEA method is able to provide the combustion engine valve failure risk complete with its degree of failure risk. In addition, it gives a better flexibility for an engineers for designing a risk assessment tools. As a result, incorporating FMEA technique in Fuzzy Logic according to the combustion engine valve case study, will give a more reliable and flexible combustion engine valve failure risk reducing process.